ERADICATION OF CRIMINAL ACTS OF CORRUPTION TOWARDS DIRECTORS OF COMMANDITAIRE VENNOOTSCHAP WHO PERFORM CRIMINAL ACTS OF CORRUPTION - Sibghatullah BW, As'ad Djaelani (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
This study aims to determine and to qualify criminal acts of corruption within article 2 and article 3 of Law Number 31 Year 1999 On Eradication of Criminal Acts of Corruption, and to determine the application of material criminal law and legal considerations by the judges in deciding the verdict The statute approach, which examines laws that are related to research problems, is the approach used in this normative research. In addition to the statue approach, the author also carries out a case approach, which means that this research is complemented by a review of the judge's considerations in the decision. The primary and secondary materials obtained were then analyzed descriptively to then be presented qualitatively. This research concluded that: 1) Article 2 and Article 3 of the Law of 1999 has several differences. One of the differences can be found on the subject. Article 2 applies to anyone who commits the act and Article 3 applies to anyone with a